Funkcija influensera u digitalnom novinarstvu / Influencers Function in Digital Journalism: Implikacije djelovanja novih mrežnih aktera na novinarstvo / The Implications of New Network Actors on Journalism - Duraković, Jasna (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Traditional journalism and the media are in constant uncertainty, which is caused by the influence of social media, networks and influencers. Social networks have become a global communication phenomenon and over time they have proven to be a useful source for discovering and tracking news. In addition, online media through social networks have opened a new space for the influence of Influencers. Following this new trend of development and use of social networks, the audience is more aware of the increasing use of Facebook as a news source, and at the same time the increasing influence of Influencers, who are changing the reputation of journalism by creating informative posts and statuses. Value of influencers is reflected in the fact that by their commenting on daily events, political decisions and news from the news portals about them; they directly raise the popularity of this media content within the audience, which further followes them, likes and shares their posts. Influencers greatly promote the informative content of individual online media, so they provide greater visibility, increase reading of this media content, and with their comments on these contents they draw more public attention, furthermore extending lifespan of these news.